Intermittent runs at the velocity associated with maximal oxygen uptake enables subjects to remain at maximal oxygen uptake for a longer time than intense but submaximal runs - Billat, V. L.; Slawinski, J.; Bocquet, V.; Demarle, A.; Lafitte, L.; Chassaing, P.; Koralsztein, J. P. (European Journal of Applied Physiology, 2000)
The purpose of this study was to compare the times spent at VO2max during an interval training programme and during continuous strenuous runs. Eight long-distance runners took part in three maximal tests on a synthetic track (400 m) whilst breathing through a portable, telemetric metabolic analyser: they comprised firstly, an incremental test which determined vLT, VO2max [59.8 (SD 5.4) ml · min-1 · kg-1], vVO2max [18.5 (SD 1.2) km · h-1], secondly, an interval training protocol consisting of alternately running at 100% and at 50% of vVO2max (30 s each); and thirdly, a continuous high intensity run at vLT + 50% of the difference between vLT and vVO2max [i.e. v<Delta>50: 16.9 (SD 1.00) km · h-1 and 91.3 (SD 1.6)% vVO2max]. The first and third tests were performed in random order and at 2-day intervals. In each case the subjects warmed-up for 15 min at 50% of vVO2max. The results showed that in more than half of the cases the v<Delta>50 run allowed the subjects to reach VO2max, but the time spent specifically at VO2max was much less than that during the alternating low/high intensity exercise protocol [2 min 42 s (SD 3 min 09 s) for v<Delta>50 run vs 7 min 51 s (SD 6 min 38 s) in 19 (SD 5) interval runs]. The blood lactate responses were less pronounced in the interval runs than for the v<Delta>50 runs, but not significantly so [6.8 (SD 2.2) mmol · l-1 vs 7.5 (SD 2.1) mmol · l-1]. These results do not allow us to speculate as to the chronic effects of these two types of training at VO2max.